Biotextiles for Biomedical Applications: A Review - Heitor Luiz Ornaghi Júnior; Julia Pradella Garavatti (Textiles, 2025)
The demand for healthcare and medical devices increases as the population ages. With the advance of textile science and technology, new products have been developed to replace the traditional ones, including biotextiles. This review has the objective of presenting biotextiles for biomedical applications, specifically drug delivery systems, medical implants, and regenerative medicine, showing the scientific progress in the respective fields, some relevant scientific studies, and commercially available products. The aim is to present to readers a quick overview guide for reference, including future trends and challenges.